FACTORS INFLUENCING GEN Z’S PERCEPTION TOWARD PUBLIC FIGURES: A CONCEPTUAL STUDY ON SOCIAL MEDIA ENGAGEMENT, AUTHENTICITY, SOCIO-POLITICAL STANCE, AND CELEBRITY ENDORSEMENT - Ahmad , Nurul Afiqah; Esa , Nawal Esa Yazid; Abdul Rahman, Azura; Haron, Hazliza; Rasak, Nor Tasnim Syahera; Nazmi, Farhana Mohd (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2025)
This conceptual paper explores the factors shaping Generation Z’s perceptions of public figures, with a particular focus on social media engagement, authenticity, socio-political stances, and celebrity endorsements. As a generation raised in a digital environment, Gen Z connects with public figures mostly through social media platforms, where both curated content and real-time interactions influence how they form opinions and emotional bonds. The paper looks closely at authenticity, suggesting that when public figures are transparent, relatable, and willing to show vulnerability, they are more likely to gain Gen Z’s trust and admiration. It also considers how socio-political stances taken by public figures can influence their perception, especially when those stances reflect values that matter deeply to Gen Z, such as climate change, social justice, and equality. Celebrity endorsements are examined as well, not only in terms of promotional impact but also in relation to how well they align with the public figure’s personal brand and the social relevance of the endorsed message. When this alignment is strong, credibility tends to be enhanced, while a lack of alignment may lead to scepticism or reduced influence. By bringing together insights from existing literature and theoretical frameworks, this study offers a thoughtful and nuanced understanding of how these variables interact and what they mean for public figures, brands, and social influence strategies that aim to resonate with this socially aware and digitally fluent generation.